Iron Neurotoxicity and Protection by Deferoxamine in Intracerebral Hemorrhage - Li, Zhe; Liu, Yang; Wei, Ruixue; Khan, Suliman; Zhang, Ruiyi; Zhang, Yan; Yong, Voon Wee; Xue, Mengzhou (Frontiers in Molecular Neuroscience, 2022)
Intracerebral hemorrhage (ICH) is a subtype of stroke that is characterized by high morbidity and mortality, for which clinical outcome remains poor. An extensive literature indicated that the release of ferrous iron from ruptured erythrocytes in the hematoma is a key pathogenic factor in ICH-induced brain injury. Deferoxamine is an FDA-approved iron chelator that has the capacity to penetrate the blood-brain barrier after systemic administration and binds to iron. Previous animal studies have shown that deferoxamine attenuates ICH-induced brain edema, neuronal death, and neurological deficits. This review summarizes recent progress of the mechanisms by which deferoxamine may alleviate ICH and discusses further studies on its clinical utility.